Clinical utility and patient considerations in the use of ofatumumab in chronic lymphocytic leukemia - Frustaci AM (Dove Medical Press, 2015)
Anna Maria Frustaci, Alessandra Tedeschi, Paola Picardi, Roberto Cairoli, Marco MontilloDepartment of Hematology, Niguarda Cancer Center, Niguarda Ca' Granda Hospital, Milan, Italy Abstract: Treatment aim for chronic lymphocytic leukemia has been radically changed over the past years from providing only a palliative approach to reaching disease eradication and improving survival. Ofatumumab is a monoclonal humanized antibody with peculiar in vitro and in vivo properties, at present approved for double fludarabine and alemtuzumab refractory chronic lymphocytic leukemia. Its efficacy in this subset of patients, who typically have an unfavorable prognosis, facilitated its use in different Phase II and III trials. Ofatumumab as single agent or combined with chemotherapeutic or biologic agents, led to sundry results in the setting of both previously treated or untreated patients. Its role in maintenance therapy is also under investigation. Further advances concerning ofatumumab administration as first line therapy in combination with chlorambucil, came recently from the COMPLEMENT 1 study. Results from this trial will open the door to new perspectives of its use in treatment-naïve patients. Ofatumumab was well tolerated in almost all the studies, with the main adverse events relating mostly to infusion reaction. Hematologic toxicity, especially neutropenia, was also common. A significant improvement in patients' quality of life was reported following ofatumumab treatment and this was mainly due to its effect on constitutional symptoms. Nevertheless, some concerns remain regarding the long-term efficacy of the drug in terms of response duration and survival. The real strength of this drug needs to be confirmed by further studies and direct comparative trials. Keywords: ofatumumab, chronic lymphocytic leukemia, refractory, alemtuzumab, fludarabine, high risk